Genomic Evolution, Patterns of Global Dissemination, and Interspecies Transmission of Human and Simian T-cell Leukemia/Lymphotropic Viruses - Slattery, Jill Pecon; Franchini, Genoveffa; Gessain, Antoine (Genome Research, 1999)
Using both env and long terminal repeat (LTR) sequences, with maximal representation of genetic diversity within primate strains, we revise and expand the unique evolutionary history of human and simian T-cell leukemia/lymphotropic viruses (HTLV/STLV). Based on the robust application of three different phylogenetic algorithms of minimum evolution–neighbor joining, maximum parsimony, and maximum likelihood, we address overall levels of genetic diversity, specific rates of mutation within and between different regions of the viral genome, relatedness among viral strains from geographically diverse regions, and estimation of the pattern of divergence of the virus into extant lineages. Despite broad genomic similarities, type I and type II viruses do not share concordant evolutionary histories. HTLV-I/STLV-I are united through distinct phylogeographic patterns, infection of 20 primate species, multiple episodes of interspecies transmission, and exhibition of a range in levels of genetic divergence. In contrast, type II viruses are isolated from only two species (Homo sapiens and Pan paniscus) and are paradoxically endemic to both Amerindian tribes of the New World and human Pygmy villagers in Africa. Furthermore, HTLV-II is spreading rapidly through new host populations of intravenous drug users. Despite such clearly disparate host populations, the resultant HTLV-II/STLV-II phylogeny exhibits little phylogeographic concordance and indicates low levels of transcontinental genetic differentiation. Together, these patterns generate a model of HTLV/STLV emergence marked by an ancient ancestry, differential rates of divergence, and continued global expansion.